2018
DOI: 10.1186/s12877-018-0743-1
|View full text |Cite
|
Sign up to set email alerts
|

First and second eye cataract surgery and driver self-regulation among older drivers with bilateral cataract: a prospective cohort study

Abstract: BackgroundDriving a car is the most common form of transport among the older population. Common medical conditions such as cataract, increase with age and impact on the ability to drive. To compensate for visual decline, some cataract patients may self-regulate their driving while waiting for cataract surgery. However, little is known about the self-regulation practices of older drivers throughout the cataract surgery process. The aim of this study is to assess the impact of first and second eye cataract surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 42 publications
(49 reference statements)
0
21
0
Order By: Relevance
“…), which was also the case in previous studies conducted with other ocular diseases. 8 , 13 Strabismus surgery was shown to significantly improve patient self-confidence, as evidenced by a significant improvement in the self-confidence questionnaire for driving. In total, the analysis of self-confidence for the driving questionnaire showed that 80% of patients believed that strabismus surgery had a positive impact on driving ability.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…), which was also the case in previous studies conducted with other ocular diseases. 8 , 13 Strabismus surgery was shown to significantly improve patient self-confidence, as evidenced by a significant improvement in the self-confidence questionnaire for driving. In total, the analysis of self-confidence for the driving questionnaire showed that 80% of patients believed that strabismus surgery had a positive impact on driving ability.…”
Section: Discussionmentioning
confidence: 96%
“…Patients with cataracts have been found to be more frequently responsible for road accidents than the general population, while reducing their driving time. 8 , 9 Regarding glaucoma, poor on-road driving performance with a trend to spontaneously give up driving has been observed, and simulator-based studies have revealed an increased number of eye movements and driving difficulties in particular conditions (night, fog, rain, and highway). 10 13 …”
Section: Introductionmentioning
confidence: 99%
“…For the CEDAR Study, a total of 111 participants were recruited consecutively from three public hospitals in Western Australia (WA) and completed the first assessment. Previous papers have been published from this study based on the naturalistic driving data collected17–19; a falls diary component20 and further examinations of driving simulator performance are also planned. The current analysis of physical activity outcomes includes only 55 participants who completed the first, second and third assessments.…”
Section: Methodsmentioning
confidence: 99%
“…In functional terms, cannabis seems to alter important visual parameters, including visual acuity, contrast sensitivity, colour discrimination, ocular movements, and stereoscopic perception [ 12 , 17 , 21 , 22 , 23 , 24 , 25 ]. Previous evidence has shown that visually impaired drivers adopt some modifications in their driving behaviour as a strategy to compensate for their decreased visual capacity [ 26 , 27 , 28 ]. These modifications include avoiding driving on highways or reducing their speeds [ 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%